2014
DOI: 10.1071/ch13701
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anthranilic Diamide Insecticides: Design, Synthesis, and Insecticidal Evaluation

Abstract: Three series of new anthranilic diamide derivatives containing sulfide, N-cyanomethylsulfilimine, and N-cyanomethylsulfoximine groups were designed and synthesized by coupling the active substructures of anthranilic diamides and sulfoxaflor. The structures of the synthesized compounds were confirmed by infrared spectroscopy, 1 H and 13 C NMR, and elemental analysis. Several unique structural characteristics were revealed via the crystal structure analysis of compoundBioassay results indicated that most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…The nitrated product 9 was readily converted to thiomethylated aniline 11 by reaction sequence previously used [31,33,34]. Then, 2-amino-3-methyl-5-(methylthio)benzoic acid 11 was coupled with 3-bromo-1-(3-chloropyridin-2-yl)-1 H -pyrazole-5-carboxylic acid 13 [12,14,33,34] to give the desired benzoxazinone 12 in good yield [13]. After ring opening reaction of 12 with methylamine [12,14,29,30,34], 4-methylthio anthranilamide 14 was readily obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nitrated product 9 was readily converted to thiomethylated aniline 11 by reaction sequence previously used [31,33,34]. Then, 2-amino-3-methyl-5-(methylthio)benzoic acid 11 was coupled with 3-bromo-1-(3-chloropyridin-2-yl)-1 H -pyrazole-5-carboxylic acid 13 [12,14,33,34] to give the desired benzoxazinone 12 in good yield [13]. After ring opening reaction of 12 with methylamine [12,14,29,30,34], 4-methylthio anthranilamide 14 was readily obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of alkyl sulfilimine- and sulfoximine-substituted insecticides [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. …”
Section: Figures Scheme and Tablesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The unique properties make sulfoximinesa ttractive for life science projects directedt owards medicinal and crop protection applications. [2,3] Therefore, sulfoximines have been introduced as antibiotics, antithrombotics, and tumor metastasis inhibitors. [2] In the contexto ft his study,i ti sn oteworthy that various N-(hetero)arylsulfoximines showeda nticancer activity [4] and that some derivatives with this N-substitution pattern proved applicable as agrochemicals.…”
mentioning
confidence: 99%
“…Especially compound D (Figure 1) displayed 100% larvicidal activities at 0.25 mg/l , which reached the same larvicidal level as Flubendiamide. Later, Fan et al [13] reported that anthranilic diamides structures containing N-cyano sulfiliminyl moieties also could maintain the activity. The results prompted us to look for new structures with better insecticidal potency by structure optimization.…”
mentioning
confidence: 99%